Service provision by agri-cooperatives engaged in high value markets - Donovan, J.; Stoian, D.; Foundjem, D.; Blare, T. (Global Forum for Rural Advisory Services, 2018)
Markets for agricultural products with special quality, environmental, and social attributes can provide a profitable outlet for poor farmers in developing countries. However, participation in high value markets requires that farmers commit to deliver pre-identified volumes on time and in the required form and quality – a tall order in many cases. Agricooperatives play an important role in linking farmers to these markets; they forge business relations with distant buyers, realise economies of scale in processing and marketing, and provide advisory and other services to help their members respond to buyer demands (see Box 1). Examples of these services include technical assistance, training, and input and credit provision.